Combination of Preoperative Multimodal Image Fusion and Intraoperative Dyna CT in Percutaneous Balloon Compression of Trigeminal Ganglion for Primary Trigeminal Neuralgia: Experience in 24 Patients - Liao, Chang-chun; Li, Jia-yan; Wu, Kai-hua; Jian, Zhi-heng; YI, Xin-feng; Weng, Zhi-jian; Chen, Gang (Frontiers in Surgery, 2022)
Objective: We retrospectively assessed the surgical results of PBC with preoperative multimodal image fusion and intraoperative Dyna Computed Tomography(CT) in 24 patients with primary trigeminal neuralgia (PTN) to explore a valuable aid for Percutaneous balloon compression (PBC) . Methods: We studied the data of 24 patients with PTN. All patients underwent PBC and were assessed with preoperative multimodal image fusion [computed tomography (CT) and magnetic resonance imaging (MRI)] and intraoperative Dyna CT in the Department of Neurosurgery of Zhuhai People’s Hospital between October 2020 and September 2021. Multimodal image fusion—three-dimensional (3D) reconstruction of CT and MRI data—was performed using 3D-Slicer software, and preoperative evaluation was performed according to the results of image fusion. Dyna CT was used to dynamically observe the position and shape of the metallic hollow introducer and Fogarty catheter and balloon during the operation to guide the operation in real time. We performed follow-up assessments each month and summarized the clinical characteristics, surgical effects, and complications in all patients. Results: Surgery was successful for all patients; the patients reported immediate pain relief. Surgical complications included facial numbness in 24 patients (100%), mild masseter weakness in three (12.5%), herpes zoster in three (12.5%), and balloon rupture in one (4.2%). None of the patients had serious surgical complications. The mean follow-up time was 9.6±2.7 months. During the follow-up period, 22 patients (91.7%) experienced no recurrence of pain, and two patients (8.3%) experienced recurrence of pain, of which one underwent secondary PBC surgery. Conclusions: Preoperative multimodal image reconstruction can help fully evaluate PBC surgery, clarify the etiology, and predict the volume of contrast medium required during the operation. It provided important assistance for PBC treatment of trigeminal neuralgia patients when preoperative multimodal image fusion is combined with intraoperative Dyna CT.